Critical Dynamics in Spontaneous Resting-State Oscillations Are Associated With the Attention-Related P300 ERP in a Go/Nogo Task - Herzog, Nadine D.; Steinfath, Tim P.; Tarrasch, Ricardo (Frontiers in Neuroscience, 2021)
Sustained attention is the ability to continually concentrate on task-relevant information, even in the presence of distraction. Understanding the neural mechanisms underlying this ability is critical for comprehending attentional processes as well as neuropsychiatric disorders characterized by attentional deficits, such as ADHD. In this study, we aimed to investigate how trait-like critical oscillations during rest relate to the P300 evoked potential – a biomarker commonly used to assess attentional deficits. We measured long‐range temporal correlations (LRTC) in resting-state EEG oscillations as index for criticality of the signal. In addition, attentional performance of the subjects was assessed as reaction time variability (RTV) in a continuous performance task following an oddball paradigm. P300 amplitude and latencies were obtained from EEG recordings during this task. We found that, after controlling for individual variability in task performance, LRTC were positively associated with P300 amplitudes but not latencies. In line with previous findings good performance in the sustained attention task was related to higher P300 amplitudes and earlier peak latencies. Unexpectedly, we observed a positive relationship between LRTC in ongoing oscillations during rest and RTV indicating that greater criticality in brain oscillations during rest relate to worse task performance. In summary, our results show that resting state neuronal activity, which operates near a critical state, relates to the generation of higher P300 amplitudes. Brain dynamics close to criticality potentially foster a computationally advantageous state which promotes the ability to generate higher ERP amplitudes.